Pengaruh Dosis Pupuk Cair Green Tonik Terhadap Pertumbuhan dan Produksi Tomat Karina (Solanum Lycopersicum) - Hendrikus Darwin Beja; Yovita Yasintha Bolly (Fakultas Pertanian, Universitas Nusa Nipa, 2024)
A study was conducted in Ihigetegera Village, Sikka Regency. The purpose of this study was to determine the effect of Green Tonic liquid fertilizer dosage on the growth and production of Karina tomatoes, and to determine the optimal dosage of Green Tonic liquid fertilizer that can achieve optimal production for Karina tomatoes. The treatments in this study included no fertilizer (control), 1 cc-1 fertilizer dosage, 3 cc-1 fertilizer dosage, 5 cc-1 fertilizer dosage, and 7 cc-1 fertilizer dosage. The results showed that Green Tonic fertilizer treatment significantly affected the number of leaves at 8 and 10 weeks after planting. It significantly affected plant height at 8 weeks after planting but had no significant effect at 10 weeks after planting. It significantly affected the number of fruits at 10 weeks after planting and significantly affected the fresh weight of fruits at 11 weeks after planting. The 3 cc-1 Green Tonic fertilizer dosage in this study was the best treatment for achieving the highest production of Karina tomatoes.